The effect of the political connections of government bank CEOs on bank performance during the financial crisis - Chen, Hung-Kun; Liao, Yin-Chi; Lin, Chih-Yung; Yen, Ju-Fang (Journal of Financial Stability, 2018)
This study investigates how the political connections of government bank CEOs affected their banks’ performance during the 2007–2009 financial crisis. Examination of global data shows that government banks with politically connected CEOs experienced significantly higher loan default rates and worse operating performance during the crisis than those without politically connected CEOs. However, these politically connected CEOs were less likely than others to be penalized for the poor performance of their banks. Our evidence suggests that politically connected CEOs of government banks can influence a bank’s lending decisions by using their political power and influence to relax lending standards and to reap private benefits that thus raise their banks’ sensitivity to a crisis.